Negative electrode binder, negative electrode slurry, negative electrode plate and secondary battery
By introducing a first group containing O, N, S, and P elements into the negative electrode binder, the transition metal ions are chelated, and the problem of metal ion deposition in the prior art is solved, and the cycling performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202510028471.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing negative electrode binder cannot effectively suppress the deposition of transition metal ions on the negative electrode surface, resulting in a decrease in the retention rate of the battery's cycle capacity.
By introducing a copolymer as the negative electrode binder, the first group in the copolymer contains O, N, S, and P elements, which are used to chelate metal elements and effectively absorb and chelate free transition metal ions.
It effectively reduces the deposition of metal ions on the negative electrode sheet, maintains the original structure and performance of the negative electrode material, and improves the storage and cycling performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode binder, a negative electrode slurry, a negative electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion batteries have the advantages of high voltage, high specific energy, stable discharge voltage, good cycle performance, good safety performance, and long service life, and are widely used in power vehicles, energy storage and other fields. In the cycle of secondary batteries, it is inevitable that a certain amount of transition metal ions will dissolve into the electrolyte. These dissolved transition metal ions may diffuse and be reduced and deposited on the surface of the negative electrode, thereby destroying the solid electrolyte interface film (SEI film) on the surface of the negative electrode, causing the battery's cycle capacity retention rate to decrease.
[0003] The active material layer of the existing negative electrode is obtained by coating the negative electrode slurry on the surface of the negative electrode current collector, drying, rolling and slitting. The negative electrode slurry includes negative electrode active material, conductive agent and negative electrode binder, wherein the negative electrode binder is generally SBR, which has the function of increasing the peeling strength with the current collector on the one hand and maintaining the cohesion of the negative electrode sheet on the other hand, and does not have the function of inhibiting the deposition of metal ions on the negative electrode surface.
[0004] Therefore, how to reduce the amount of transition metal ions diffused to the negative electrode surface to improve the storage and cycle performance of the battery is an urgent problem to be solved. Summary of the invention
[0005] The present invention aims at the problem that the existing negative electrode binder cannot inhibit the deposition of transition metal ions on the negative electrode surface. The present invention provides a negative electrode binder, a negative electrode slurry, a negative electrode sheet and a secondary battery.
[0006] To solve the above technical problems, the present invention provides a negative electrode binder, including a copolymer, wherein the copolymer includes a first group, the first group is used to chelate metal elements, and the first group contains at least one of O, N, S, and P elements.
[0007] Preferably, the first group is selected from at least one of an amino group, an imine group, a tertiary amine group, an amide group, a hydroxyl group, a carboxyl group, a carbonyl group, a thiol group, a sulfamoyl group, a thiourea group, a sulfite group, and a phosphonic acid group.
[0008] Preferably, the negative electrode binder is formed by polymerization of monomers, wherein the monomers include a first monomer containing a first group and a second monomer reacting with the first monomer, wherein the second monomer contains an unsaturated double bond and a functional group capable of undergoing a condensation reaction, and the functional group capable of undergoing a condensation reaction is selected from one or more of a hydroxyl group, an amino group, a carboxyl group, and a siloxane group.
[0009] Preferably, the first monomer is selected from one or more of humic acid, fulvic acid, citric acid, EDTA, 2,6-bis(2-benzimidazolyl)pyridine, amino acids, α-aminophosphonates, bis-α-aminopropylphosphonates, 1-hydroxyethylidene-1,1-diphosphonic acid, DO3A-thiol, ninhydrin, 4,4'-bis(2-amino-benzenesulfonic acid)bisphenol A ester, 3-hydroxyphenylthiourea, sodium N,N-dicarboxylic acid amino-2-hydroxypropane sulfonate, tetrasodium 3-hydroxy-2,2'-iminodisuccinate, and zoledronic acid; And / or, the second monomer is selected from one or more of hydroxyethyl acrylate, acrylamide, acrylic acid, methacrylic acid, methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, and vinylguanamine.
[0010] Preferably, the types of the first groups in the negative electrode binder are the same or different.
[0011] Preferably, the average particle size of the negative electrode binder is 0.05-1 μm.
[0012] In a second aspect, the present application provides a negative electrode slurry, comprising a negative electrode active material and a negative electrode binder as described in any one of the above.
[0013] Preferably, based on 100% by mass of the negative electrode slurry, the mass content of the negative electrode binder is 1% to 3%.
[0014] Preferably, the negative electrode slurry further comprises a water-soluble polymer, and the water-soluble polymer comprises one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and modified substances thereof.
[0015] In a third aspect, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer is formed by coating the negative electrode slurry described in any one of the above items.
[0016] In a fourth aspect, the present application provides a secondary battery comprising a positive electrode sheet, an electrolyte and the negative electrode sheet as described above, wherein the free metal ion content in the electrolyte is <10 ppm, and the free metal ions are one or more of Fe, Mn, Th, Hg, Cu, and Ni.
[0017] In the present application, the binder is modified by introducing a first group, and the O, N, S or P atoms in the first group are complexed with transition metal ions, so that the binder can effectively absorb and chelate free transition metal ions to avoid deposition on the negative electrode main material, thereby improving the storage and cycle performance of the battery. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] An embodiment of the present application provides a negative electrode binder, including a copolymer, wherein the copolymer includes a first group, the first group is used to chelate metal elements, and the first group contains at least one of O, N, S, and P elements.
[0020] In this embodiment, the binder is modified by introducing a first group, and the O, N, S or P atoms in the first group are complexed with transition metal ions, so that the binder can effectively absorb and chelate free transition metal ions to avoid deposition on the negative electrode main material, thereby improving the storage and cycle performance of the battery.
[0021] In some embodiments, the first group is selected from at least one of an amino group, an imine group, a tertiary amine group, an amide group, a hydroxyl group, a carboxyl group, a carbonyl group, a thiol group, a sulfamoyl group, a thiourea group, a sulfite group, and a phosphonic acid group.
[0022] By complexing the transition metal ions in the electrolyte with the above-mentioned first group, the deposition of metal ions on the negative electrode sheet is effectively reduced, which helps to maintain the original structure and performance of the negative electrode material and maintain the normal diffusion channel of lithium ions in the negative electrode, thereby improving the storage and cycle performance of the battery.
[0023] In some embodiments, the negative electrode binder is formed by polymerization of monomers, wherein the monomers include a first monomer containing a first group and a second monomer reacting with the first monomer, wherein the second monomer contains an unsaturated double bond and a functional group capable of undergoing a condensation reaction, and the functional group capable of undergoing a condensation reaction is selected from one or more of a hydroxyl group, an amino group, a carboxyl group, and a siloxane group.
[0024] The first monomer undergoes a polycondensation reaction with the second monomer, thereby introducing the first group in the first monomer into the binder, so that the binder can effectively absorb and chelate free transition metal ions. The addition of the second monomer can also improve the peeling force of the negative electrode sheet, further improving the electrical performance and service life of the battery. At the same time, the polar functional group in the second monomer makes the negative electrode have better conductivity, making the battery internal resistance smaller, and having better cycle performance and rate performance.
[0025] In some embodiments, the monomer further comprises a third monomer, and the third monomer comprises an olefin monomer and an acrylate monomer. The negative electrode binder is obtained by polycondensation or polyaddition reaction between the first monomer, the second monomer and the third monomer. The olefin monomer and the acrylate monomer exist in the negative electrode binder as olefin units and acrylate units.
[0026] The olefin monomer is selected from one or more of maleic acid, styrene, α-methylstyrene, vinyltoluene, 2-vinylnaphthalene, methylvinylnaphthalene, vinylanthracene, methylvinylanthracene, phenoxyethyl methacrylate, 2-butylene ethoxy phthalate, benzyl acrylate, 2-phenoxyethyl acrylate, biphenyl acrylate, phenoxydiethylene glycol acrylate, ethoxy polyethylene glycol o-phenylphenol acrylate, benzyl methacrylate, ethoxylated bisphenol A dimethacrylate, phenyl acrylate, and benzyl acrylate.
[0027] The acrylic acid ester monomer is selected from one or more of methoxydiethylene glycol methacrylate, stearic methacrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, 2-methoxyethyl acrylate, isopentyl acrylate, amyl acrylate, octyl acrylate, hexyl acrylate, isopropyl acrylate, isodecyl acrylate, butyl acrylate, hexadienyl acrylate, vinyl acrylate, 3,4-epoxycyclohexyl methacrylate, methylhexyl acrylate, allylhexyl acrylate, formyloxyethyl acrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, behenyl acrylate, behenyl methacrylate, and caprolactone acrylate.
[0028] Further, in some embodiments, the mass ratio of the third monomer to the second monomer is (20-150): (20-200).
[0029] In some embodiments, the first monomer is selected from one or more of humic acid, fulvic acid, citric acid, EDTA, 2,6-bis(2-benzimidazolyl)pyridine, amino acids, α-aminophosphonates, bis-α-aminopropylphosphonate, 1-hydroxyethylidene-1,1-diphosphonic acid, DO3A-thiol, ninhydrin, 4,4'-bis(2-amino-benzenesulfonic acid) bisphenol A ester, 3-hydroxyphenylthiourea, sodium N,N-dicarboxylic acid amino-2-hydroxypropane sulfonate, tetrasodium 3-hydroxy-2,2'-iminodisuccinate, and zoledronic acid.
[0030] The second monomer is selected from one or more of hydroxyethyl acrylate, acrylamide, acrylic acid, methacrylic acid, methacryloxypropyl trimethoxysilane, methacryloxypropyl triethoxysilane, and vinylguanamine. By selecting the first monomer, the binder can effectively absorb and chelate free transition metal ions.
[0031] In some embodiments, the molar ratio of the first monomer to the second monomer is (0.1-10): (5-20). By controlling the molar ratio of the first monomer to the second monomer, the first monomer and the second monomer can undergo a condensation polymerization reaction.
[0032] In some embodiments, the types of the first groups in the negative electrode binder are the same or different, so as to absorb and chelate different types of transition metal ions.
[0033] In some embodiments, the average particle size D50 of the negative electrode binder is 0.05-1 μm. Specifically, the negative electrode binder is in the form of an emulsion, and its solid content is 30%-60%. By controlling the particle size of the negative electrode binder within the above range, the negative electrode binder can be evenly dispersed in the negative electrode slurry.
[0034] An embodiment of the present application provides a negative electrode slurry, comprising a negative electrode active material and a negative electrode binder as described in any one of the above embodiments. Compared with adding additional compounds for chelating metal ions or coating the negative electrode material, this embodiment reduces production costs and improves economic benefits.
[0035] In some embodiments, based on 100% by mass of the negative electrode slurry, the mass content of the negative electrode binder is 1% to 3%, so as to ensure that the transition metal ion concentration in the electrolyte is within a suitable range.
[0036] In some embodiments, the negative electrode slurry further includes a water-soluble polymer, and the water-soluble polymer includes one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and modified substances thereof. The viscosity of the negative electrode slurry is adjusted by adding the water-soluble polymer to ensure the uniformity of the negative electrode slurry coating.
[0037] In one embodiment, the volume median particle size D50 of the negative electrode active material is 1-20 μm.
[0038] An embodiment of the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer is formed by coating the negative electrode slurry described in any one of the above items.
[0039] An embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, an electrolyte and the negative electrode sheet as described above, wherein the free metal ion content in the electrolyte is less than 10 ppm, and the free metal ions are one or more of Fe, Mn, Th, Hg, Cu, and Ni.
[0040] The free metal ions in the electrolyte are complexed with the negative electrode binder in the negative electrode sheet, thereby reducing the free metal ion content in the electrolyte by 20%~80%, making the free metal ion content in the electrolyte less than 10ppm, reducing the deposition of metal ions on the negative electrode sheet, thereby improving the storage and cycle performance of the battery.
[0041] The present invention is further described below by way of examples.
[0042] The negative electrode binder, negative electrode and secondary battery disclosed in the present invention are specifically described.
[0043] Example 1 Binder The first monomer humic acid, the second monomer hydroxyethyl acrylate, and benzenesulfonic acid (catalyst) were mixed and reacted at 80°C for 10 hours to form monomer 1. Then 50 parts of monomer 1 were mixed with 1 part of maleic acid and 50 parts of butyl acrylate, and then added to the pre-emulsification kettle, and stirring was started for high-speed pre-emulsification to obtain a uniform pre-emulsified liquid, and the pre-emulsified liquid was transferred to a constant pressure dropping funnel for standby use.
[0044] Add deionized water and surfactant into the reactor and mix them evenly, then introduce high-purity nitrogen as protective gas to replace the air; then start heating the reactor, stir while heating, and add initiator (ammonium persulfate) when the temperature in the reactor reaches the first reaction temperature of 70°C. After the initiator is added, open the constant pressure dropping funnel and start dropping the pre-emulsified liquid for reaction. Keep stirring on and pass nitrogen during the reaction. The stirring rate during the reaction is 50r / min, and the emulsification reaction time is 7h.
[0045] After the emulsification reaction is completed, the temperature is continued to rise to the second reaction temperature of 90°C, and stirring is continued for heat preservation and aging. Nitrogen is continuously introduced during the aging process. During the aging process, the stirring rate is 100r / min and the aging time is 5h. After the aging is completed, it is naturally cooled to room temperature and then filtered to obtain the negative electrode binder. The molar ratio of the first monomer to the second monomer is 1:1, and the first group in the binder is hydroxyl and carboxyl.
[0046] Negative plate 96% of negative electrode active material graphite, 1% of negative electrode conductive agent conductive carbon black, 1.5% of water-soluble polymer sodium carboxymethyl cellulose and 1.5% of binder are mixed, and deionized water is added for stirring to prepare negative electrode slurry. Then the negative electrode slurry is coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, the negative electrode sheet is obtained.
[0047] Positive electrode The positive electrode active material lithium manganese oxide, conductive carbon black, and positive electrode binder are mixed in a mass ratio of 90:3:7, and NMP is added to prepare positive electrode slurry. The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet.
[0048] Secondary battery preparation The negative electrode sheet, separator (PE film), and positive electrode sheet are wound in sequence so that the separator is placed between the positive and negative electrodes to play an isolating role, and the electrode assembly is made. The electrode assembly is placed in an outer package, and commercially available electrolyte is injected and packaged. After that, a secondary battery is obtained through processes such as liquid injection, formation, and exhaust.
[0049] Example 2 Most of the steps of Example 2 are the same as those of Example 1, except that the first monomer is 2,6-di(2-benzimidazolyl)pyridine, the second monomer is acrylic acid, and the first group is an amino group.
[0050] Example 3 Most of the steps of Example 3 are the same as those of Example 1, except that the first monomer is α-aminophosphonate, the second monomer is methacrylic acid, and the first group is a phosphate group.
[0051] Example 4 Most of the steps of Example 4 are the same as those of Example 1, except that the first monomer is an amino acid, the second monomer is vinylguanamine, and the first group is an amino group.
[0052] Example 5 Most of the steps of Example 5 are the same as those of Example 1, except that the first monomer is DO3A-thiol, the second monomer is acrylamide, and the first group is a thiol.
[0053] Example 6 Most of the steps of Example 6 are the same as those of Example 1, except that the first monomer is 3-hydroxyphenylthiourea, the second monomer is acrylic acid, and the first group is thiourea.
[0054] Example 7 Most of the steps of Example 7 are the same as those of Example 1, except that the first monomer is 4,4'-bis(2-amino-benzenesulfonic acid) bisphenol A ester, the second monomer is acrylic acid, and the first group is sulfamic acid group.
[0055] Example 8
[0056] Most of the steps of Example 8 are the same as those of Example 1, except that the first monomer is EDTA, the second monomer is methacryloxypropyltrimethoxysilane, and the first group is a carboxyl group and a tertiary amine group.
[0057] Example 9 Most of the steps of Example 9 are the same as those of Example 1, except that the first monomer is citric acid, the second monomer is methacryloxypropyltrimethoxysilane, and the first group is carboxyl or hydroxyl.
[0058] Example 10 Most of the steps of Example 10 are the same as those of Example 1, except that the first monomer is 1-hydroxyethylidene-1,1-diphosphonic acid, the second monomer is acrylic acid, and the first group is a phosphate group.
[0059] Embodiment 11 Most of the steps of Example 11 are the same as those of Example 1, except that the first monomer is ninhydrin, the second monomer is acrylic acid, and the first group is hydroxyl.
[0060] Example 12 Most of the steps of Example 12 are the same as those of Example 1, except that the first monomer is sodium N,N-dicarboxylic acid amino-2-hydroxypropane sulfonate, the second monomer is acrylic acid, and the first group is amino group.
[0061] Example 13 Most of the steps of Example 13 are the same as those of Example 1, except that the first monomer is zoledronic acid, the second monomer is acrylamide, and the first group is a phosphate group.
[0062] Embodiment 14 Most of the steps of Example 14 are the same as those of Example 1, except that the molar ratio of the first monomer to the second monomer is 1:2.
[0063] Embodiment 15 Most of the steps of Example 15 are the same as those of Example 1, except that the molar ratio of the first monomer to the second monomer is 1:50.
[0064] Example 16 Most of the steps of Example 16 are the same as those of Example 1, except that the molar ratio of the first monomer to the second monomer is 1:200.
[0065] Embodiment 17 Most of the steps of Example 17 are the same as those of Example 1, except that the amount of binder added to the negative electrode slurry is 1%.
[0066] Embodiment 18 Most of the steps of Example 18 are the same as those of Example 1, except that the amount of binder added to the negative electrode slurry is 3%.
[0067] Embodiment 19 Most of the steps of Example 19 are the same as those of Example 1, except that the amount of binder added to the negative electrode slurry is 5%.
[0068] Comparative Example 1 Most of the steps of Comparative Example 1 are the same as those of Example 1, except that the first monomer is not contained.
[0069] Electrode and electrical performance test: The negative electrode sheets and secondary batteries prepared in the above examples and comparative examples were subjected to the following tests.
[0070] 1) Negative electrode peel strength test: The coated single-sided negative electrode sheet was heated at 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating was fixed on the tape on the steel plate with the surface facing down. After rolling back and forth 6 times with a 2.5kg roller, the coating and copper foil were torn off. The upper plate clamped the copper foil side and stretched at a speed of 50mm / min and 180°C. The data of the stable tension section was recorded as the peel strength (N / m).
[0071] 2) Test of transition metal ion content in electrolyte after cycling: Inductively coupled plasma emission spectrometry (ICP) was used to measure the concentration of transition metal ions in the electrolyte of the battery after 50 cycles, and the total concentration was calculated. The transition metal ions include nickel metal ions, cobalt metal ions, manganese metal ions and iron metal ions.
[0072] 3) Normal temperature cycle test The specific method is: after placing the battery in a constant temperature test room at 25℃±2℃ for 1h, charge it to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C; discharge it to 2.5V at 1C constant current, and record the discharge capacity; repeat the above steps 500 times, and calculate the capacity retention rate.
[0073] The above test results are shown in Table 1 below.
[0074] Table 1
[0075] From the above results, it can be concluded that the use of the binder of the structure can have a good enrichment effect on metal ions while maintaining a high peeling force, so that the metal ions in the electrolyte are reduced to a large extent, thereby ensuring the improvement of the cycle performance. Without using the binder of the first monomer, the peeling force is slightly reduced. In addition, the content of metal impurities in the electrolyte increases significantly, which has a great impact on the cycle performance of the battery. From Examples 1, 15, and 16, it can be seen that as the content of the second monomer increases, the peeling force of the negative electrode sheet increases, the absorption of impurity ions also increases, and the cycle performance improves. From Examples 17-19, it can be seen that as the amount of binder used in the system increases, the peeling force shows an upward trend, and the absorption of metal ions also improves, but because excessive binder use will affect the cycle performance, the cycle performance of Example 19 will decrease to a certain extent.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode binder, characterized in that: The copolymer includes a first group, the first group is used for chelating metal elements, and the first group contains at least one of O, N, S, and P elements.
2. The negative electrode binder according to claim 1, characterized in that The first group is selected from at least one of an amino group, an imino group, a tertiary amine group, an amide group, a hydroxyl group, a carboxyl group, a carbonyl group, a thiol group, a sulfamoyl group, a thiourea group, a sulfite group, and a phosphonic acid group.
3. The negative electrode binder according to claim 2, characterized in that: The negative electrode binder is formed by polymerization of monomers, wherein the monomers include a first monomer containing a first group and a second monomer reacting with the first monomer, wherein the second monomer contains an unsaturated double bond and a functional group capable of undergoing a condensation reaction, and the functional group capable of undergoing a condensation reaction is selected from one or more of a hydroxyl group, an amino group, a carboxyl group, and a siloxane group.
4. The negative electrode binder according to claim 3, characterized in that The first monomer is selected from one or more of humic acid, fulvic acid, citric acid, EDTA, 2,6-bis(2-benzimidazolyl)pyridine, amino acids, α-aminophosphonates, bis-α-aminopropylphosphonates, 1-hydroxyethylidene-1,1-diphosphonic acid, DO3A-thiol, ninhydrin, 4,4'-bis(2-amino-benzenesulfonic acid)bisphenol A ester, 3-hydroxyphenylthiourea, sodium N,N-dicarboxylic acid amino-2-hydroxypropane sulfonate, tetrasodium 3-hydroxy-2,2'-iminodisuccinate, and zoledronic acid; And / or, the second monomer is selected from one or more of hydroxyethyl acrylate, acrylamide, acrylic acid, methacrylic acid, methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, and vinylguanamine.
5. The negative electrode binder according to claim 1, characterized in that The types of the first groups in the negative electrode binder are the same or different.
6. A negative electrode slurry, characterized in that: The invention comprises a negative electrode active material and the negative electrode binder according to any one of claims 1 to 5.
7. The negative electrode slurry according to claim 6, characterized in that: Taking the mass content of the negative electrode slurry as 100%, the mass content of the negative electrode binder is 1% to 3%.
8. The negative electrode slurry according to claim 6, characterized in that: The negative electrode slurry further includes a water-soluble polymer, and the water-soluble polymer includes one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid and modified products thereof.
9. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode active material layer is formed by coating the negative electrode slurry according to any one of claims 6 to 8.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, an electrolyte and the negative electrode sheet according to claim 9, wherein the free metal ion content in the electrolyte is less than 10 ppm, and the free metal ions are one or more of Fe, Mn, Th, Hg, Cu and Ni.
Citation Information
Patent Citations
Lithium battery electrode plate and preparation method thereof
CN109560254A
Novel binder material with block structure side chain and preparation method thereof
CN112382756A
Binder and preparation method thereof, electrode plate, secondary battery and electric device
CN116875227A
Binder, negative plate comprising binder and battery
CN117736668A
Lithium ion battery
US20140242452A1
Cited By
Negative electrode binder, negative electrode slurry, negative electrode sheet, and secondary battery
WO2026149246A1